Exploration of Khushal Khan Khattak's Poetry with the Perspective of Civilization - Khan, Qudrat Ullah; Shah, Syed Zubair (sourcecoder, 2023)
A notable figure in Pashto literature and linguistics is Khushal Khan Khattak. He established the groundwork for Pashto linguistics and literature. He gained international recognition for bringing diversity to Pashto poetry. Translations of his poetry have been published in other international languages. He was proclaimed the poet of the Afghan monarchy by Allama Muhammad Iqbal, the poet of the East. The Pashto culture, civilization, way of life, manners, kindness, courage, and warship are all vividly shown in his poetry. His poetry also touches on behaviourism, psychology, and resistance. Khushal Khan Khattak's poetry embodies the civic spirit of Pashtoon civilization. His poetry conveys a message of bravery, freedom, hospitality, and kindness. He uses multiple levels of significance to deliver his message and reveal the Pashtoon Civilization's cultural connotations. The cultural significance of the Pashtoon Civilization, which is ingrained in this region and is passed down from generation to generation, is examined in this article.